A biocatalytic peptidobiosensing molecular bridge for detecting osteosarcoma marker protein - Jing, Pengwei; Wang, Ying; Sun, Weixue; Li, Guishi; Zhang, Zuofu; Xu, Qiang; Li, Hao (Frontiers in Chemistry, 2023)
A biosensing scheme requiring only one-step sample incubation before signal collection, and using a compact “three-in-one” probe of target-binding, signal conversion, and amplification, may greatly simplify the design of biosensors. Therefore, sparing the multi-step addition of enzymes, protein, and nanomaterial, as well as the associated complexity and non-specific interactions. In this work, a peptide probe aimed at such compact features has been designed, based on protein-triggered, conformation-driven, and Cu (II) facilitated side-chain di-tyrosine cyclization. This design can use target-probe recognition to induce discriminated cross-linking and self-cleavage of the probe, resulting in retention or dissociation of a signal amplification motif from the search and consequently quantitative detection performance. The method has also been tested preliminarily in fractioned osteosarcoma clinical samples, showing an acceptable coherence between signal readout and clinical diagnosis. On the basis of these early findings, it is reasonable to assume that the proposed probe will be beneficial for the next development of tumor screening and prognosis sensors.